Elasticity modulus, hardness and fracture toughness of Ni3Sn4 intermetallic thin films - Chen, Zhong (2012)
Intermetallic compounds (IMCs) are present in microelectronic solder interconnects as a result of interfacial reaction between the solder and the metallization materials. Their mechanical properties are of great interest for the prediction of joint reliability of electronic packages. In this work, thin film Ni3Sn4 IMCs were formed by co-sputtering of Sn and Ni, followed by annealing at different temperatures. Elasticity modulus and hardness of the films were investigated by nano-indentation. It was found that measured hardness decreased with increasing residual tensile stress in the film. The elasticity modulus of the Ni3Sn4 thin films was measured to be around 134 GPa by nano-indentation. The fracture toughness of these Ni3Sn4 thin films varied considerably with the annealing temperature. It ranged from 2.11 ± 0.15 MPa m1/2 for 100 °C annealing to 5.75 ± 0.25 MPa m1/2 for 200 °C annealing. Densification during annealing is believed to be the cause of the increase in toughness.